Helically and Linearly Fused Rylenediimide‐Hexabenzocoronenes. Issue 21 (10th March 2021) - Dusold, Carolin; Haines, Philipp; Platzer, Benedikt; Guldi, Dirk M.; Hirsch, Andreas
Abstract: Perylene‐ as well as naphthalenediimides were fused to hexabenzocoronenes (HBCs) at their imide position to realize highly π‐extended donor–acceptor (D–A)‐hybrids. Successful isomer separation in the first step was decisive to guarantee a straightforward synthetic sequence. Hexaphenylbenzenes as precursors were accessed via Diels–Alder reactions and reacted in a Scholl oxidation to yield the respective HBC derivatives. The fully conjugated benzimidazole linker, which separates the electron donating HBC from the electron accepting rylenediimide, enabled the formation of either a linear or a helical configuration. Largely different chemical, physical, and optoelectrical characteristics were noted for the two configurations. What stood out was their aggregation and their excited state deactivation depending on the solvent polarity. Results from global analysis of the femtosecond transient absorption data corroborated the formation of a charge‐transfer (CT) state that is stabilized in the helically fused configuration relative to the linear analogue. However, a comparison with spectroelectrochemical experiments failed to disclose evidence for a charge‐separated (CS) state. Abstract : Fantastic fusion : The fusion of naphthalene‐ as well as perylenediimides and hexabenzocoronenes via a fully conjugated benzimidazole linker enables the formation of helical as well as linear π‐extended donor–acceptor‐hybrids applying Diels–Alder and Scholl‐type chemistry. Remarkable differences in aggregation, charge‐transfer (CT) stabilization as well as CT lifetimes emphasize the influence of the configuration of the bridge on donor–acceptor properties.